ANALISIS USAHA PENGOLAHAN KERUPUK IKAN GABUS (Channa Striata Bloch) PESERTA PROGRAM PEMBERDAYAAN KONSULTAN KEUANGAN MITRA BANK (KKMB) DI KALIMANTAN SELATAN (STUDI PEMBERDAYAAN KKMB DI KOTA BANJARMASIN) - Muhammad Aini; Idiannor Mahyudin; Emmy Sri Mahreda (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
This research aimed to analyze the technology performance of the snakehead crackers processing business in Banjarmasin City after participating in KKMB empowerment program; to compare the incomes of the snakehead crackers processors in Banjarmasin City before and after participating in KKMB empowerment program; to analyze the factors affecting the incomes of the snakehead crackers processors in Banjarmasin City after participating in KKMB empowerment program; to analyze the market opportunities of the snakehead crackers processed by program participants; and to identify the marketing channels of the snakehead crackers processed by program participants.This research was carried out in Banjarmasin City, South Kalimantan, with theobjects of the snakehead crackers processors participating in KKMB empowerment program. The data that was collected was the data that directly originated from results of observation in the location of the research, and the other supporting data, was related tothe object of the research. Results of the research showed that the technology performance of the snakehead crackers processing business had grown well in Banjarmasin City after participating in KKMB empowerment program, characterised by the increasing quantity and quality ofproduction. Incomes of the snakehead crackers processors in Banjarmasin City after participating in program had increased, showed by the incomes increasing an average of189.79% from before participating in program. Income of the snakehead crackers processors in Banjarmasin City was significantly affected by the processed fish volume, the amount ofthe loan capital and business scale, which the regression coefficient of the each variable was positive and valid on test level of 99%. The average difference between the supply and demand of 4,65 tons/year indicated that the snakehead crackers marketing in Banjarmasin City still had a large market opportunity to keep organised. The marketing channels of the snakehead crackers processed by program participants in Banjarmasin City were consist of three pattern of the marketing channels, i.e. producers to consumers directly, producers through the collectors the retailers, and producers through the retailers before distributed to consumers.